Evaluation of the Cavite City Library and Museum - Mojica, Michael Anthony A. (2000)
The purpose and objectives of the public library are described in relation to three basic concerns - the needs of the people who use the libraries, the need to ensure that the library is located in a suitable site, and the need for effective means for operating it and developing its services (Mahapatra and Thomas 1996). The Cavite City Library and Museum was established by the city government to serve as an information and learning center. An evaluation of this library would greatly promote its development according to the Minimum Standards for Public Libraries and to the functions and objectives of a public library. The objective of this study is to find out the nature of the collection of the library, to ascertain if the library meets the information needs of its clients, to find out if the library meets the Minimum Standards for Public Libraries set by the PLAI, to identify the areas where the library fails to meet the standards, to know the strengths and weaknesses of the library.